Price pressures - Terrence Hendershott; Albert J. Menkveld (Goethe University Frankfurt, Center for Financial Studies (CFS), 2010)
We study price pressures in stock prices-price deviations from fundamental value due to a risk-averse intermediary supplying liquidity to asynchronously arriving investors. Empirically, twelve years of daily New York Stock Exchange intermediary data reveal economically large price pressures. A 100,000 inventory shock causes an average price pressure of 0.28% with a half-life of 0.92 days. Price pressure causes average transitory volatility in daily stock returns of 0.49%. Price pressure effects are substantially larger with longer durations in smaller stocks. Theoretically, in a simple dynamic inventory model the 'representative' intermediary uses price pressure to control risk through inventory mean reversion. She trades off the revenue loss due to price pressure against the price risk associated with remaining in a nonzero inventory state. The model's closed-form solution identifies the intermediary's relative risk aversion and the distribution of investors' private values for trading from the observed time series patterns. These allow us to estimate the social costs-deviations from constrained Pareto efficiency-due to price pressure which average 0.35 basis points of the value traded.
urn:nbn:de:hebis:30-78662
Keywords: G12; G14; D53; D61; 330; Liquidity; Inventory Risk; Intermediary; Volatility; Börsenkurs; Volatilität; Finanzintermediär; Risikoaversion; Marktliquidität; Wertpapiergeschäft; Schock; Schätzung; USA